mTOR Deletion Alleviates CD4+ T-Cell Dysfunction in Sepsis through Reducing CTLA4 Accumulation Mediated by Rescuing Autophagy - Xianli Lei; Guoyu Zhao; Yawen Xie; Na Cui (Mediators of Inflammation)
Sepsis has been the leading cause of death in ICU patients. CD4+ T cells are the mainstay of the body’s immune system, and the depletion of CD4+ T cells in sepsis is of great concern. Cytotoxic T lymphocyte-associated protein 4 (CTLA4) is a negative immunomodulator for T cell activation and degradation through the autophagy-lysosome pathway. Mammalian target of rapamycin (mTOR) is the most classical upstream regulator of autophagy. With a mouse model of sepsis through cecal ligation and puncture (CLP), T cell specific-mTOR/tuberous sclerosis complex 1 (TSC1)-knockout mice, and bafilomycin A1, a specific autophagosome-lysosome (A-L) fusion inhibitor, we primarily proved that mTOR could modulate the expression and accumulation of CTLA4 by regulating the onset process of autophagy such as A-L fusion. Given such a regulatory relationship, targeting mTOR could provide new light to improve immune function in sepsis, and the prospect of using rapamycin in the clinic would be worth exploring further.